Use of Helical TomoTherapy for the Focal Hypofractionated Treatment of Limited Brain Metastases in the Initial and Recurrent Setting - Elson, Andrew; Walker, Ashley; Bovi, Joseph A.; Schultz, Christopher (Frontiers in Oncology, 2015)
BACKGROUND Whole brain radiation therapy (WBRT), stereotactic radiosurgery (SRS) or both are commonly employed in the treatment of limited brain metastases in the initial or recurrent setting. Hypofractionated partial volume irradiation is also employed, however published experience using HT for this purposes is limited. We reviewed our institutional experience to assess patient selection factors, fractionation scheme, and outcomes associated with this technique. METHODS A retrospective chart review was performed to evaluate patients treated with partial volume hypofractionated HT-based IMRT for brain metastases at our institution. RESULTS Thirteen patients (7M/6F, median age 62, median KPS 90) with a limited (1-9) number of brain metastases in the primary or recurrent setting were identified. Primary malignancies included colorectal (3), NSCLC (5), RCC (1), breast (1), melanoma (1), uterine (1) and ovarian (1). The median time from initial diagnosis to brain metastases was 20.7 months (range 0-61.3). Treatment was delivered to intact metastases in 6 patients, to a single resection cavity in 6 patients, and to both in one patient. A total of 27 lesions were treated. The median number of intact metastases treated was 2 (range 1-9). Previous treatments included WBRT (5), WBRT+SRS (3), SRS alone (1), and none (4). The most common fractionation schemes were 25 Gy in 5 fractions and 27.5 Gy in 5 fractions to each lesion. At a median of 6 months follow up (range 1.26-20.13) after TomoTherapy, 10 patients were deceased, 2 were alive and 1 was lost to follow up. The median intracranial progression free survival and overall survival after TomoTherapy was 6.3 months. Freedom from local failure for treated lesions was 71% and 59% at 6 and 12 months CONCLUSIONS TomoTherapy-based hypofractionated radiotherapy is associated with acceptable disease control and survival outcomes and represents a viable treatment option in the primary and recurrent setting for select patients.